Pengaruh Persistensi Laba, Ukuran Perusahaan dan Leverage Terhadap Kualitas Laba - Amelia Cahya Pratiwi; Sri Layla Wahyu Istanti (Al-Buhuts, 2026)
This study aims to analyze the influence of earnings persistence, firm size, and leverage on earnings quality in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from annual financial reports published via the IDX. The sample was selected using a purposive sampling technique based on established criteria, resulting in six companies observed over a five-year period, yielding 30 units of analysis. Earnings quality, the dependent variable, is measured using an income quality metric, while the independent variables consist of earnings persistence, firm size, and leverage. Data analysis was conducted using multiple linear regression. The results indicate that earnings persistence has a positive but insignificant effect on earnings quality, with a regression coefficient of 1.494 and a significance value of 0.240. Firm size has a negative but insignificant effect on earnings quality, with a regression coefficient of -0.003 and a significance value of 0.842. Meanwhile, leverage has a positive and significant effect on earnings quality, with a regression coefficient of 0.989 and a significance value of 0.003. The Adjusted R² value of 0.208 indicates that earnings persistence, firm size, and leverage collectively explain 20.8% of the variation in earnings quality, while the remaining 79.2% is explained by factors outside the research model. These findings demonstrate that leverage is a factor that contributes significantly to earnings quality in the food and beverage companies studied.